Research Progress of Inter-Domain SDN Inter-Networking Technology WE-Bridge and Its Testbed - Jun Bi (Dianxin kexue)
Firstly three phases of the development of inter-domain SDN internetworking were discussed, then a cooperation based inter-domain SDN technology WE-Bridge was introduced. Finally, an inter-continental inter-domain SDN testbed based on WE-Bridge technology was introduced.